Gender disparity in health-related quality of life among people living with HIV/AIDS in Ethiopia: a systematic review and meta-analysis - Tufa, Derara Girma; Tola, Habteyes Hailu; Dissassa, Hiwot Dejene; Geleta, Leta Adugna; Malka, Erean Shigign; Tadesse, Addisu Waleligne; Wariso, Feyiso Bati; Fetensa, Getahun (Frontiers in Global Women's Health, 2024)
IntroductionHealth-related quality of life (HRQoL) is a key outcome indicator in antiretroviral therapy program. In Ethiopia, primary studies on gender disparity in HRQoL among people living with HIV/AIDS (PLHA) are conflicting, with no pooled estimation. Therefore, this study aimed to investigate gender disparity in HRQoL among PLHA in Ethiopia.MethodsStudies were retrieved from PubMed, Web of Science, SCOPUS, Embase, MEDLINE, Science Direct, HINARI, and PsycINFO were systematically searched. In addition, Google Scholar, Google, journal homepages, bibliographies, and universities' research repositories in the country were searched by combining keywords and Medical Subject Headings (MeSH) terms with Boolean operators. Based on the primary study results, the average score of each domain was utilized as a cut-off point to classify HRQoL as poor or good. The Joanna Briggs Institute (JBI) checklist was used to assess study quality. A random-effects model was used to report the pooled estimates. Summary estimates are presented in forest plots and tables. The variation between studies was assessed using the Higgins heterogeneity test (I2). Funnel plot, Begg's test, and Egger's test were used to assess publication bias. Data were extracted using Microsoft Excel and exported to STATA 17 (Corporation, College Station, TX, USA) for analysis. The search results were managed using the EndNote X7 software.ResultsFifteen studies with 4,867 PLHA were included. The pooled prevalence of poor HRQoL was 46.53% (95% CI: 41.96–51.10), 46.15% (95% CI: 37.05–55.24), and 36.21% (95% CI: 30.19–42.23) among PLHA, women, and men living with HIV, respectively. Moreover, a significant gender disparity in HRQoL was observed among Ethiopian women and men living with HIV. Women living with HIV were found to have 61% increased odds of poor HRQoL than men living with HIV in the country (OR = 1.61, 95% CI: 1.07, 2.15). No statistical evidence of a publication bias was observed.ConclusionAlmost half of PLHA patients in Ethiopia had a poor HRQoL. Women living with HIV have higher odds of poor HRQoL than men living with HIV. This highlights the pressing need for gender-specific risk assessment approaches and treatment interventions aimed at optimizing HRQoL in HIV/AIDS settings.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023454810.